Analisis Kestabilan Lereng Andesit Menggunakan Metode FEM pada PT. X - Ruslan Loilatu; Iswandaru (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. Geotechnical study data collection includes geotechnical mapping, observations of landslide models that can occur, and sampling for testing physical and mechanical properties. The geotechnical study carried out is by analyzing slides on production slopes, the analytical method used in the analysis of landslides on slopes is the kinematic method, analysis with this method uses rock mass parameters, discontinuity planes, and production slope geometry as input. The overall slope stability analysis using the Finite Element Method (FEM) shows the overall slope is in a stable condition seen from the value of the Safety Factor (FK) which is 1.26. For single slope stability analysis, the slope is modeled with three variations of slope and three variations of height to determine the minimum limit of optimal slope geometry. For slopes with optimal conditions compared to the other two variations of angles, namely slopes with a slope of 50° and a maximum height of 10 m with an SRF of > 1.25 which is used as an optimal slope recommendation, the slope with that slope if modeled with several variations in height, namely 5 m has an SRF of 2.02, a height of 10 m has an SRF of 1.48, and a height of 15 m has an SRF of 1.28, which shows the three variations in height using a slope of 50° have an FK value > 1.25, whereas if the height is made to exceed the limit a height of 15 m, the slope has the potential for landslides. Abstrak. Pengumpulan data studi geoteknik meliputi pemetaan geoteknik, pengamatan model longsoran yang dapat terjadi, dan melakukan sampling untuk pengujian sifat fisik dan sifat mekanik. Kajian geoteknik yang dilakukan adalah dengan menganalisis kelongsoran pada lereng produksi, metode analisis yang digunakan dalam analisis longsoran pada lereng adalah metode kinematik, analisis dengan metode ini menggunakan input parameter massa batuan, bidang diskontinuitas, dan geometri lereng produksi. Analisis kestabilan lereng keseluruhan menggunakan Finite Element Method (FEM) menunjukan lereng keseluruhan dalam kondisi stabil dilihat dari nilai Faktor Keamanan (FK) yang didapatkan sebesar 1,26. Untuk analisis kestabilan lereng tunggal lereng dimodelkan dengan tiga variasi kemiringan dan tiga variasi ketinggian untuk mengetahui batas minimum geometri lereng yang optimal. Untuk lereng dengan kondisi yang optimal dibandingkan dua variasi sudut yang lain adalah lereng dengan kemiringan 50° dan tinggi maksimum 10 m dengan SRF sebesar >1,25 yang dijadikan sebagai rekomendasi lereng yang optimal, lereng dengan kemiringan tersebut jika dimodelkan dengan beberapa variasi ketinggian yaitu 5 m memiliki SRF sebesar 2,02 , ketinggian 10 m memiliki SRF 1,48, dan ketinggian 15 m memiliki SRF sebesar 1,28, yang menunjukan ketiga variasi ketinggian dengan menggunakan kemiringan 50° memiliki nilai FK >1,25, sedangkan jika ketinggian dibuat melebihi batas ketinggian 15 m maka lereng berpotensi longsor.